Contextual Effect of School on the Risk Obesity among High School Students in Surakarta, Central Java: A Multilevel Analysis Evidence - Rita Setiyaningsih; Yulia Lanti Retno Dewi; Rita Benya Adriani (Journal of Epidemiology and Public Health, 2019)
Background: Obesity is a public health problem in various countries, one of which is Indonesia. The impact of obesity in adulthood is high blood pressure and high cholesterol which can later trigger cardiovascular disease. This study aimed to examine contextual effect of school on the risk obesity among high school students in Surakarta. Subjects and Method: This was an observational analytic study with a case control approach. The study was conducted in April 2019. The sample was selected by stratified random sampling of 225 students in 15 schools in Surakarta with a case and control group. The dependent variable was obesity. The independent variables were parental salary, parental knowledge, pocket money, school food environment, food intake, physical activity, maternal BMI, paternal BMI. Data collection techniques used questionnaires and analyzed by multilevel logistic regression in Stata 13.Results: Obesity in adolescents was directly and significantly affected by parental income ?Rp 1,800,000 (OR= 4.53; 95% CI= 1.80 to 11.36; p = 0.001), high parental knowledge (OR= 0.36; 95% CI= 0.15 to 0.91; p= 0.030), allowance ?Rp 10,000 (OR= 3.80; 95% CI= 1.63 to 8.86; p= 0.002), food intake ?recommended dietary allowances (OR= 3.62; 95% CI= 1.43 to 9.19; p = 0.007), high physical activity (OR= 0.06; 95% CI= 0.02 to 0.18; p <0.001), maternal BMI >27kg/m